Loneliness and Cognitive Distortion in Adolescent Facebookers - Rani Agias Fitri; Syerlie July Anggita (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2015)
Facebook users in Indonesia dominated by adolescents in the age range 12 - 15 years. The usage of Facebook has negative effects, such as loneliness and cognitive distortion. The study aims to determine the relationship between loneliness and cognitive distortions in early adolescence Facebook users. Using revision of UCLA Loneliness Scale (ULS) – 8 (Hays & DiMatteo, 1987) and Briere’s (2000) Cognitive Distortion Scale (CDS), data was collected from 146 early adolescents, female and male, who studied at schools in East Jakarta, South Jakarta, North Jakarta, and Depok. Based on results of data analysis using Spearman Rank correlation. A significant positive correlation was obtained between loneliness and cognitive distortion on early adolescence Facebook users (r= .271, p< .005). It was supported by a significant positive correlation between dimension of cognitive distortion (self criticism, self blame, helplessness, hopelessness, and preoccupation with danger) and loneliness with correlation rate .234 – .308.